Historical Analysis of Civil-Military Relations in Nepal - K.C., Khadga (Tribhuvan University Journal, 2013)
As like in other developing democracies, it is obvious that there are many CMR problems in Nepal. A lack of national security policies and common national interests, ignorance about security sensitiveness, political instability, parochialism, mistrust, are prominent factors contributing to Nepal’s adverse civil-military relations. However, the military though has already begun to tuning with democratic norms and values should further be engaged in serious organizational reform that includes among others; enhancing professionalism, further accountability, transparency and loyalty of army to the civilian authority follow by earliest promulgation of democratic constitution with the clear provision of democratic control over armed forces.